DEVELOPMENT OF BUSINESS INCUBATOR MANAGEMENT INFORMATION SYSTEM AT UNSOED BUSINESS INCUBATOR CENTER - lasmedi afuan; Arief Kelik Nugroho; Muhammad Randy Cahya Mardika (Informatika, Universitas Jenderal Soedirman, 2022)
The Unsoed Business Incubator Center (PIB) is one of the incubation centers under the General Sudirman University Community Service Institute. PIB Unsoed aims to help develop the businesses of MSMEs and Startups around the Jenderal Sudirman University area. In the incubation process, of course, there is a lot of data recording related to the tenant incubation process, such as administrative data, data development, data assistance, and other data related to the tenant incubation process. The process of recording data on PIB Unsoed is still done manually without any technological aids such as computers or cellphones. In addition, at PIB Unsoed, there are often cases of data loss regarding the business incubation process that has taken place at PIB Unsoed. From the background of the problem above, the author wants to create a Business Incubator Assistance Management Information System for PIB Unsoed. This system is based on a website using the Laravel framework and developed using a prototyping development method. The results of the research that has been done can be concluded that the Management Information System for managing the Business Incubator can be implemented at PIB UNSOED.